Direct integration of MEMS, dielectric pumping and cell manipulation with reversibly bonded gecko adhesive microfluidics. (4th August 2016) - Warnat, S; King, H; Wasay, A; Sameoto, D; Hubbard, T
Abstract: We present an approach to form a microfluidic environment on top of MEMS dies using reversibly bonded microfluidics. The reversible polymeric microfluidics moulds bond to the MEMS die using a gecko-inspired gasket architecture. In this study the formed microchannels are demonstrated in conjunction with a MEMS mechanical single cell testing environment for BioMEMS applications. A reversible microfluidics placement technique with an x - y and rotational accuracy of  ±2 µ m and 1° respectively on a MEMS die was developed. No leaks were observed during pneumatic pumping of common cell media (PBS, sorbitol, water, seawater) through the fluidic channels. Thermal chevron actuators were successful operated inside this fluidic environment and a performance deviation of ~15% was measured compared to an open MEMS configuration. Latex micro-spheres were pumped using traveling wave di-electrophoresis and compared to an open (no-microfluidics) configuration with velocities of 24 µ m s −1 and 20 µ m s −1 .